Comparative assessment of neurotoxicity impacts induced by alkyl tri‐n‐butyl phosphate and aromatic tricresyl phosphate in PC12 cells. Issue 12 (14th July 2020) - Chang, Yeqian; Cui, Haiyan; Jiang, Xiaofeng; Li, Mei
Abstract: Organophosphate flame retardants (OPFRs) have become a growing concern due to their potential environmental and health risk. However, limited studies have described the toxicity, particularly neurotoxicity of alkyl and aromatic OPFRs. This study investigated the neurotoxicity of alkyl tri‐n‐butyl phosphate (TnBP) and aromatic tricresyl phosphate (TCP) to rat adrenal pheochromocytoma (PC12) cells for 24 h. Viability detection showed dose‐response toxicity effect of TCP and TnBP to PC12 cells. The half‐maximal inhibitory concentration of 24 h (24 h‐IC50 ) of TCP and TnBP were 2415.61 and 338.09 μM, respectively. Both TnBP and TCP significantly changed the acetylcholinesterase (AChE) activity, and TnBP is more likely to cause neurotoxicity to PC12 cells compared to TCP. Also, The results of LDH and caspase‐3 activity detection as well as Hoechst staining suggested that cell apoptosis induced by TCP and TnBP may be the primary pathway. These findings provide a toxicity data of aromatic and alkyl‐substituted OPFRs to PC12 cells, and a new insight into the toxicity of OPFRs on health risk assessment.